Toll-like Receptor Activation Remodels the Polyamine and Tryptophan Metabolism in Porcine Macrophages - Meimei Zhang; Lingfei Du; Yinhao Shen; Peng Bin (Metabolites)
Background: The early nutritional metabolism of piglets is intimately associated with the regulation of immune function, and amino acids play a crucial role in modulating the fate and function of porcine immune cells, especially macrophages. However, the metabolic changes upon macrophage activation remain elusive. Methods: We established an in vitro activation model of porcine macrophages and investigated alterations in metabolites involved in polyamine and tryptophan metabolism upon activation by various toll-like receptor (TLR) activators. Results: TLR activation inhibits the production of spermine and alters the kynurenine pathway of the tryptophan metabolism toward the kynurenic acid biosynthesis. Specifically, TLR9 activation redirects the metabolic pathway of tryptophan toward kynurenic acid synthesis, which subsequently inhibits melatonin production via the protein kinase A (PKA)/cyclic adenosine monophosphate (cAMP)/cAMP-responsive element-binding protein (CREB) signaling pathways. Conclusions: TLR activation reprograms the polyamine and tryptophan metabolism in porcine macrophages. Knowledge of the metabolic alterations in polyamine and tryptophan upon TLR activation in macrophages offers valuable insights and potential strategies for nutritional intervention to enhance piglet immunity.